Non-Bayesian updating: A theoretical framework - Larry G. Epstein; Jawwad Noor; Alvaro Sandroni (Theoretical Economics, 2008)
This paper models an agent in a multi-period setting who does not update according to Bayes' Rule, and who is self-aware and anticipates her updating behavior when formulating plans. Choice-theoretic axiomatic foundations are provided to capture updating biases that reflect excessive weight given to either prior beliefs, or alternatively, to observed data. A counterpart of the exchangeable Bayesian learning model is also described.
Keywords: D81; 330; Non-Bayesian updating; temptation and self-control; overreaction; underreaction; learning; law of small numbers